Identification of anti-osteoclastogenic compounds from Cleistocalyx operculatus flower buds and their effects on RANKL-induced osteoclastogenesis. (September 2019) - Tran, Phuong Thao; Ngo, Thi Quynh-Mai; Lee, Suhyun; Kim, Okwha; Tran, Huynh Nguyen Khanh; Hwangbo, Cheol; Min, Byung Sun; Lee, Jeong-Hyung
Graphical abstract: Highlights: The anti-osteoclastogenic effect of Cleistocalyx operculatus is demonstrated. Ethanol extract of C. operculatus flower buds (ECB) inhibits RANKL-induced osteoclastogenesis. Eight compounds are identified as anti-osteoclastogenic compounds from ECB. Maslinic acid and its two coumaroyl analogs inhibit RANKL-induced NFATc1 activation. The mechanism explains the anti-osteoclastogenic effect of C. operculatus flower buds. Abstract: Cleistocalyx operculatus flower buds are used as a main ingredient in various beverages and herbal tea in tropical areas. The present study was conducted to investigate anti-osteoclastogenic effects of ethanol extract of C. operculatus flower buds (ECB) and to identify anti-osteoclastogenic compounds in these buds. ECB significantly inhibited RANKL-induced osteoclast differentiation and decreased RANKL-induced the activation of NFATc1. We isolated nineteen compounds from C. operculatus flower buds and found that eight compounds, including maslinic acid (6 ) and its two coumaroyl analogs (7 and8 ), significantly inhibited RANKL-induced osteoclast formation. Among these, 3-O- trans - p -coumaroyl maslinic acid (8 ) showed the most potent inhibitory effect on RANKL-induced osteoclastogenesis via impairment of c-Fos and NF-κB activation, and subsequently, NFATc1 activation. These results suggested that identification of the anti-osteoclastogenic compounds from C. operculatus flower buds may extend our understanding of molecular mechanisms underlying biological activities of C. operculatus flower buds for osteoclast-related diseases.